Magnetic Susceptibility and Heavy Metal Content of Palm Oil Plantations Soil as a Function of its Depth. (October 2020) - Sinuraya, Salomo; Amiruddin, Erwin; Hutauruk, Marisayani; Fajri, Naldi Rahmat
Abstract: The magnetic susceptibility and heavy metal content of oil palm plantations soil has been determined. The magnetic particles of the soil were separated from non-magnetic particles using neodymium iron boron (NdFeB) magnet. The magnetic induction of the soil was measured using Pasco Probe PS-2162. The magnetic susceptibility value on the surface of the oil palm plantation soil varies between (685.99 to 1081.96) × 10 −5 . This value is higher than the reference soil magnetic susceptibility that is 457.30 × 10 −5 . The magnetic susceptibility values decrease as soil depth increases and at a depth of 40 cm the magnetic susceptibility value is close to the value of reference soil magnetic susceptibility. The X-Ray Fluorescence Spectroscopy (XRF) test result showed that the plantation soil has been contaminated with Cr, Fe, Ti, Sr, and V, this is in accordance with the magnetic susceptibility value of the plantation soil surface which is higher than that of the reference soil.